2015
DOI: 10.1159/000439109
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion of More than 800 kb Is the Most Recurrent Mutation in Chilean Patients with <b><i>SHOX</i></b> Gene Defects

Abstract: Background: Deletions in the SHOX gene are the most frequent genetic cause of Leri-Weill syndrome and Langer mesomelic dysplasia, which are also present in idiopathic short stature. Aim: To describe the molecular and clinical findings observed in 23 of 45 non-consanguineous Chilean patients with different phenotypes related to SHOX deficiency. Methods: Multiplex ligation-dependent probe amplification was used to detect the deletions; the SHOX coding region and deletion-flanking areas were sequenced to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The CRLF2 protein is a type 1 cytokine receptor involved in hematopoietic cell development and in the JAK-STAT pathway, active in bone metabolism and development ( Al-Shami et al 2004 ; Li 2013 ; Hanada et al 2014 ). Poggi et al (2015) reported large deletions in PAR spanning SHOX and CRLF2 in some of the LWD patients, but the common feature among LWD cases is deletions spanning SHOX . Thus, although we cannot exclude that the deletion of CRLF2 is involved in the phenotypic expression of SA, we argue that the similarity to human phenotypes caused by SHOX deficiency support the interpretation that SA is manifested by a reduction of SHOX expression.…”
Section: Discussionmentioning
confidence: 99%
“…The CRLF2 protein is a type 1 cytokine receptor involved in hematopoietic cell development and in the JAK-STAT pathway, active in bone metabolism and development ( Al-Shami et al 2004 ; Li 2013 ; Hanada et al 2014 ). Poggi et al (2015) reported large deletions in PAR spanning SHOX and CRLF2 in some of the LWD patients, but the common feature among LWD cases is deletions spanning SHOX . Thus, although we cannot exclude that the deletion of CRLF2 is involved in the phenotypic expression of SA, we argue that the similarity to human phenotypes caused by SHOX deficiency support the interpretation that SA is manifested by a reduction of SHOX expression.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genetic studies, the Laboratory of Molecular Biology and Cytogenetics at Pontificia Universidad Católica performs analyses for different genetic conditions, including variants associated with Ach, Leri‐Weill dyschondrosteosis, and TD (Mancilla et al, 2003; Poggi et al, 2015). Sequencing of selected exons of the FGFR3 gene and MLPA deletion/duplication analysis and sequencing of the SHOX gene are currently performed.…”
Section: Sd In Chilementioning
confidence: 99%
“…Among individuals with the initial diagnosis of ISS, approximately 10% harbor SHOX mutations ( Table 2 ). The results vary considerably from cohort to cohort, and the prevalence of SHOX mutations has increased with more sensitive genetic tests that can detect small deletions (eg, MLPA vs fluorescence in situ hybridization [FISH]) and with the examination of SHOX enhancer regions that were omitted in early SHOX mutation screening ( 18 , 50 , 58 , 161 , 166 , 167 , 174 , 179 , 180 , 184 , 186 , 205 207 , 209 211 ).…”
Section: Clinical Implications Of Shox Deficiencymentioning
confidence: 99%